Quality assessment of a training program for undergraduate sonography peer tutors: paving the future way for peer-assisted learning in medical ultrasound education - Weimer, Johannes; Yilmaz, Didem; Ille, Carlotta; Weinmann-Menke, Julia; Müller, Lukas; Büchner, Hans; Buggenhagen, Holger; Stäuber, Marie; Neubauer, Ricarda; Winter, Lone; Weimer, Andreas; Dirks, Klaus; et al. (Frontiers in Medicine, 2025)
IntroductionPeer tutoring has been increasingly used to support university sonography teaching, necessitating well-qualified tutors. This study aims to evaluate the quality of a training program for sonography peer tutors developed and implemented at a university hospital.Materials and methodsA training program consisting of 11 modules was developed and subsequently evaluated for success with two subjective and two objective assessments of peer-tutoring quality. The two subjective assessments measured subjective scores of the peer tutors’ specialist and didactic skills using a Likert scale (1 = very low; 7 = very high) from the perspective of the individuals the peer tutor taught (assessment 1) and from the peer tutors themselves (assessment 2). The peer tutors also rated the training concept itself. The objective assessments evaluated the peer tutors’ specialist skills with a theoretical test (assessment 3) and a practical examination (assessment 4). Data collection for assessment 1 began in 2017, while data for assessments 2 to 4 were collected from 2021 to 2024.ResultsA total of 2,980 data sets for assessment 1, 92 data sets for 2, 44 data sets for assessment 3, and 147 data sets for assessment 4 were included in the analysis. Peer tutors scored highly positively on assessments 1 [6.6 ± 0.63 scale points (SP)] and 2 (5.53 ± 0.63 SP), and these results remained consistently high throughout the semesters. Assessments 3 (74.7 ± 7.9%) and 4 (85.6 ± 10.5%) also showed strongly positive values that remained constant over time. Assessment 1 results were significantly higher than the others (p < 0.01.), while no significant differences were found between assessments 2, 3, and 4.ConclusionThe data indicate that the training concept developed established and maintained high-quality peer-tutor training throughout the reviewed semesters. Future efforts should promote the development of national and international standards for peer-tutor training and provide certification opportunities for peer tutors.